PROTOTIPE SISTEM KEAMANAN BRANKAS BERBASIS ESP32 CAM DENGAN OTENTIKASI PIN DAN DETEKSI GERAKAN - Iqbal Ardiansyah; Amirullah Moh Rumuntoha; Abdillah Raka Sakti; Erwin Apriliyanto (STMIK Subang, 2026)
The high risk of theft of valuable assets requires a more reliable storage system, given that conventional safes with physical keys or combinations still have security gaps that are vulnerable to manipulation. This study aims to design and implement a prototype of an Internet of Things (IoT)-based safe security system using ESP32-CAM equipped with PIN authentication and motion detection features. The research method applied is prototyping with an experimental approach that includes system architecture design, hardware implementation, and functionality testing. This system integrates a keypad for PIN verification, a PIR sensor to detect motion threats, and an ESP32-CAM camera for visual evidence capture. Security is enhanced through a real-time notification mechanism to Telegram and recording of activity history in the Firebase database. Test results show that the system has a PIN authentication accuracy rate of 100% for 4-8 digit variations. The motion detection feature is able to work optimally up to a distance of 150 cm with 100% success. Additionally, the system successfully sends warning notifications along with photo evidence to Telegram with an average response time under 5 seconds. This research contributes to minimizing the risk of safe break-ins through the integration of automated visual monitoring and a remote early warning system.